VoIP Performance Comparison across MPLS-Based Networks with SIP, H.323 Signaling Protocols Enhancing the QoS through RSVP Protocol (Sebha University Conference Proceedings, 2025)
This study demonstrates the application of the OPNET simulation tool to assess VoIP over MPLS networks utilizing the RSVP protocol as a QoS mechanism, with SIP or H.323 serving as signaling protocols for establishing VoIP conversations over the Internet. The findings indicated that H.323 with RSVP over MPLS networks yielded lower end-to-end delay compared to the SIP protocol, rendering it an optimal choice for signaling in VoIP over MPLS networks where minimal end-to-end delay is essential. Conversely, SIP demonstrated the least delay jitter and minimal call setup time.